Fit for war in decades: Europe's and Germany's slow rearmament vis-à-vis Russia - Guntram B. Wolff; Alexandr Burilkov; Katelyn Bushnell; Kharitonov Ivan (Kiel Institute for the World Economy (IfW Kiel), 2024)
War is back in Europe and as it becomes long-lasting, the question of armament gains central importance. This report finds that Russian military industrial capacities have been rising strongly in the last two years, well beyond the levels of Russian material losses in Ukraine. Meanwhile, the build-up of German capacities is progressing slowly. We document Germany's military procurement in a new Kiel Military Procurement Tracker and find that Germany did not meaningfully increase procurement in the one and a half years after February 2022, and only accelerated it in late 2023. Given Germany's massive disarmament in the last decades and the current procurement speed, we find that for some key weapon systems, Germany will not attain 2004 levels of armament for about 100 years. When taking into account arms commitments to Ukraine, some German capacities are even falling. The new Tracker provides detailed information on quantities, value of the orders, predicted delivery dates, as well as the companies from which Germany procures. The situation of slow and insufficient procurement can and needs to be remedied. Failing on deterrence would mean a higher likelihood of a costly war. Instead of Germany pursuing a "war economy", as some have argued, Germany's defence budget needs to durably and credibly increase. Higher and credible long-term demand will lead to increasing supply capacities. A long-term European armament strategy is needed. Germany and Europe need to focus on speed in procurement, on cost effectiveness through economies of scale in an integrated European market, on innovation, and on technological superiority. Tracking military rearmament is essential to the security of the continent. – – Der Krieg ist zurück in Europa, und je länger er andauert, desto mehr gewinnt die Frage der Aufrüstung an zentraler Bedeutung. Dieser Bericht stellt fest, dass die Kapazitäten der russischen Rüstungsindustrie in den letzten zwei Jahren stark angestiegen sind, und zwar weit über das Niveau der russischen Materialverluste in der Ukraine hinaus. Derweil schreitet der Aufbau der deutschen Kapazitäten nur langsam voran. Wir dokumentieren Deutschlands militärische Aufrüstung in einem neuen Kiel Military Procurement Tracker und stellen fest, dass Deutschland seinen Bestand an militärischen Kapazitäten in den anderthalb Jahren nach Februar 2022 nicht nennenswert erhöht und erst Ende 2023 beschleunigt hat. Angesichts der massiven Abrüstung Deutschlands in den letzten Jahrzehnten und der aktuellen Beschaffungsgeschwindigkeit wird Deutschland bei einigen wichtigen Waffensystemen erst in etwa 100 Jahren das Rüstungsniveau von 2004 erreichen. Berücksichtigt man die Rüstungsverpflichtungen gegenüber der Ukraine, sinken einige deutsche Kapazitäten sogar. Der neue Tracker liefert detaillierte Informationen über Stückzahlen, Auftragswert, voraussichtliche Liefertermine sowie über die Unternehmen, von denen Deutschland beschafft. Die Situation der langsamen und unzureichenden Beschaffung kann und muss behoben werden. Ein Scheitern bei der Abschreckung würde die Wahrscheinlichkeit eines kostspieligen Krieges erhöhen. Anstatt dass Deutschland eine "Kriegswirtschaft" betreibt, wie einige argumentiert haben, muss der deutsche Verteidigungshaushalt dauerhaft und glaubwürdig erhöht werden. Eine höhere und glaubwürdige langfristige Nachfrage wird zu steigenden Lieferkapazitäten führen. Eine langfristige europäische Rüstungsstrategie ist notwendig. Deutschland und Europa müssen sich auf Schnelligkeit bei der Beschaffung, auf Kosteneffizienz durch Größenvorteile in einem integrierten europäischen Markt, auf Innovation und auf technologische Überlegenheit konzentrieren. Die Verfolgung der militärischen Aufrüstung ist für die Sicherheit des Kontinents unerlässlich.
Keywords: H41; H56; H60; L64; N44; 330; Defence; Armament; Weapon industry; Budget; Germany; Europe; Russia